Roman Kurkiewicz jako felietonista - Mielżyńska, Agnieszka (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2011)
The article is devoted to the Roman Kurkiewicz essays. He is a philosopher, but is also a well-known newspaper, radio and television journalist. The publication “Klapsy polskie” contains selected essays printed in “Przekrój” (2006-2009). They are alphabetically arranged and concern many issues important for Poles at the time. Political, economic, sporting and cultural events are the starting point for general discussions on the human and the world. Kurkiewicz writes about difficult and controversial topics. The article describes selected examples of different kinds of essay titles. The author refers to the literature, press and TV movies. Selected examples demonstrate the richness of the author’s ideas.